The Role of The Islamic Economy in Rationalizing Consumer Behavior - Abobakr Ramadhan Salem Al Harethi (Journal of Islamic Business and Economic Review, 2019)
Our current world is prevailed by sharp tendencies towards consumption, producedby conditions and developments in the fields of production, distribution, monopoly,communication, and advertising. Consumerism is no longer confined to the developedindustrial world. But has affected many other parts of the poor and developing theworld, it has become the subject of scientific research in different knowledge systems,foremost among them economics, psychology and sociology. However, theresearchers agree that this behavior is no longer a purely individual behavior for anindependent person. But has become multiple external factors contribute to theformation, and exert various effects on the individual consumer In our contemporaryIslamic world, patterns of abuse of consumer behavior had been spread, theconsumption of things harmful to health, morals or the natural environment, thedisregard of some individuals for consumption priorities, the lack of commitment tomoderation in spending, the tendency to extravagance and luxury, These behavioralimbalances have a very negative effect on the national economy and the economies ofthe individual. it entails a waste of natural and economic resources, the disruption ofthe productive structure, the waste of human energies, this deviant consumerismreality is confirmed by the presence of factors that have shaped its current image, andby addressing them we can restore consumer behavior to its rightful place. Therefore,this study aims to study the role of the Islamic economy in rationalizing consumerbehavior, in addition to giving some suggestions.